Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/2017jd027036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stratospheric air masses on radiotracers and ozone over the central Mediterranean

Abstract: This work aims at determining the characteristics and the preferred source regions of stratospheric air masses at the Mt. Cimone World Meteorological Organization‐Global Atmosphere Watch station located in the Italian northern Apennines (44°11′N, 10°42′E, 2165 m above sea level) , a site which is considered representative of Southern Europe‐Mediterranean free troposphere. Source regions of high concentrations of 7Be, 7Be/210Pb, and O3 and regions originating high potential vorticity values are analyzed by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 203 publications
(343 reference statements)
0
10
0
Order By: Relevance
“…The spatial patterns were similar, and the source areas with higher contribution rate were mainly distributed in neighboring provinces such as Anhui, Shandong, Zhejiang provinces, etc., indicating the significance of pollution in the nearby area 37 . In addition, due to the long-range air mass transport, the contribution values of Inner Mongolia, Hebei, Gansu, Ningxia, Guangdong and Fujian provinces reached 0.5–0.8, which increased the pollutant concentrations in the study area 40 . It should be noted that the PSCF analysis did not estimate the spatial distribution of all sources.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The spatial patterns were similar, and the source areas with higher contribution rate were mainly distributed in neighboring provinces such as Anhui, Shandong, Zhejiang provinces, etc., indicating the significance of pollution in the nearby area 37 . In addition, due to the long-range air mass transport, the contribution values of Inner Mongolia, Hebei, Gansu, Ningxia, Guangdong and Fujian provinces reached 0.5–0.8, which increased the pollutant concentrations in the study area 40 . It should be noted that the PSCF analysis did not estimate the spatial distribution of all sources.…”
Section: Resultsmentioning
confidence: 89%
“…PSCF was a trajectory-based gridded statistical analysis method that can obtain the spatial distribution of pollution sources in a semi-quantitative manner 40 . The basic concept of PSCF was to combine the air mass trajectory with the atmospheric component data to generate a conditional probability in a given region which was divided into i*j small grids.…”
Section: Methodsmentioning
confidence: 99%
“…Then, in the same way, the residence time over each i, j grid cell corresponding to a measurement period under an OEE was calculated (mij). The PSCF for grid cell i, j was then computed according to Brattich et al (2017): 305 The results are shown in Figure 6, which clearly highlights the connection between the occurrence of OEEs at DA and air masses travelling over the eastern Antarctic Plateau. The PSCF values ranged from 40% to 80% in the DA region, while air masses advected from the East Antarctic Plateau were characterized by high PSCF values.…”
Section: Role Of Synoptic-scale Air Mass Transportmentioning
confidence: 99%
“…Drawing on the algorithm suggested in previous studies (e.g., Brattich et al, 2017), the potential 345 vorticity and ozone mixing ratio of different pressure altitudes (hPa) at 0:00, 6:00, 12:00, and 18:00 every day were analysed during polar night (May, Jun, July, August) at DA. If the potential vorticity of 550 hPa height over DA was greater than 2 PVU, it was considered an STT event.…”
Section: Identification Of Stt Eventsmentioning
confidence: 99%
See 1 more Smart Citation